Parallel Finite Element Simulation of Tracer lnjection in Oil Reservoirs - Coutinho, Alvaro L. G. A.; Alves, José L. D. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1995: Anais do VII Simpósio Brasileiro de Arquitetura de Computadores e Processamento de Alto DesempenhoDO - 10.5753/sbac-pad.1995.19863, 1995)
In this work, parallel finite element techniques for the simulation of tracer injection in oil reservoirs are addressed. The pressure equation is approximated by Galerkin's method and the velocity field computed through a post-processing approach to recover the required accuracy. The concentration equation is approximated in space by the Streamline Upwind Petrov Galerkin (SUPG) plus a discontinuity-capturing operator. The resulting semi-discrete equations are approximated in time by a predictor-multicorrector algorithm. The pressure, velocity and concentration linear systems of equations are solved with parallel element-by-element iterative techniques. Performance measurements on the CRAY YMP and the CRAY C90 for the injection of tracer on a five-spot pattem with random small scale permeability variations are performed to demonstrate that the numerical techniques employed are accurate and result in a fast code.